2004
DOI: 10.1002/da.20002
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure, concurrent validity, and internal consistency of the beck depression inventory?second edition in a sample of college students

Abstract: We examined the psychometric properties of the Beck Depression Inventory-Second Edition (BDI-II) [Beck et al., 1996, San Antonio: The Psychological Corporation]. Four hundred fourteen undergraduate students at two public universities participated. A confirmatory factor analysis supported the BDI-II two-factor structure measuring cognitive-affective and somatic depressive symptoms. In addition, the internal consistency was high and the concurrent validity of the BDI-II was supported by positive correlations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
393
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(425 citation statements)
references
References 7 publications
27
393
1
4
Order By: Relevance
“…Since then different items have loaded for the two-factors in a study with students (Storch, Roberti, & Roth, 2004) and in a study of the Spanish language version of the BDI-II where selfcriticalness did not load saliently and was excluded (Penley, Wiebe, & Nwosu, 2003). We found that the somatic-affective factor dominated the sample.…”
Section: Somatic-affective Vs Cognitive Factors For Depressionmentioning
confidence: 78%
“…Since then different items have loaded for the two-factors in a study with students (Storch, Roberti, & Roth, 2004) and in a study of the Spanish language version of the BDI-II where selfcriticalness did not load saliently and was excluded (Penley, Wiebe, & Nwosu, 2003). We found that the somatic-affective factor dominated the sample.…”
Section: Somatic-affective Vs Cognitive Factors For Depressionmentioning
confidence: 78%
“…The BDI‐II17, 18, 19 was used to assess level of depressive symptoms in the sample. This 21‐item instrument measures the degree of depressive symptoms, such as pessimism, agitation, and loss of energy, with most items scored on a 0 to 3 scale; 2 of the items are scored on a 0 to 6 scale and then rescaled to range from 0 to 3 before inclusion in the total.…”
Section: Methodsmentioning
confidence: 99%
“…51 Depression was assessed using the Beck's Depression Inventory (BDI) version II as a continuous variable, which has been shown to be a reliable and valid measurement of depression in different populations. [52][53][54][55] …”
Section: Methodsmentioning
confidence: 99%